Dataset_Cybervictimization_Humor_Suicidal_Ideation - Gómez García, Lucía; Quintana-Orts, Cirenia Luz; Rey-Peña, Lourdes (Universidad de Málaga, 2024)
The use of ICTs has increased in recent years, and with it, the rates of cyberbullying. This stressful event triggers psychological distress, which can lead adolescents to suicidal ideation. In the last decade, self-defeating humor has been shown to be a risk factor for both cybervictimization and suicidal ideation. However, these studies are still scarce, and it is necessary to explore this relationship. This research has two objectives: to analyze the relationships between cybervictimization, suicidal ideation and self-defeating humor; and to examine self-defeating humor as a possible moderator variable in the relationship between cybervictimization and suicidal ideation. For this, in the present study, a sample of 362 adolescents (44.75% men and 54.42% women) from southern Spain, aged between 12 and 18 years (MAge = 14.64, SD = 1.71) was evaluated through questionnaires to evaluate cybervictimization, self-defeating humor, and suicidal ideation. The data were analyzed using SPSS and the PROCESS macro (Model 1). The results showed that self-defeating humor plays a moderating role in the relationship between cybervictimization and suicidal ideation (β = .24, p < .05). This shows that at high levels of self-defeating humor, there is a greater probability that suicidal ideation will appear during adolescence in the face of the cybervictimization experience. It is important to continue researching in this direction to focus suicide prevention and intervention on replacing this maladaptive humor style with healthier humor styles and interpersonal interaction strategies
Keywords: Ciberacoso; Suicidio - Factores de riesgo; Adolescentes - Psicología; Cyberbullying; Suicide; Humor; Moderation; Teenagers